If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + y * 2 = x Reorder the terms for easier multiplication: 24 + 2y = x Solving 24 + 2y = x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 2y = -24 + x Combine like terms: 24 + -24 = 0 0 + 2y = -24 + x 2y = -24 + x Divide each side by '2'. y = -12 + 0.5x Simplifying y = -12 + 0.5x
| -25=4(5k-7)+3(1+3k) | | 6(2x+1)=12x+3 | | -2(1-10n)=-52+10n | | 48.3/17.3 | | -2(1-10n)=-27+14b | | 0.6x+1.43=x-6.22 | | 6(4b+2)+3b=-27+14b | | (2/3x)-4=5/6 | | 2/3x-4=5/6 | | 5x-25=2x-38 | | -26=4(8n+6)-2(3n-1) | | 7(7k-9)+5k=8k+29 | | 2(-2p+3)-5(p+7)=34 | | -54/g=3 | | 7a-3b+5= | | -34+x=6(-8-x) | | 6x/-4=-.3 | | -23-8x=-2(x-7)-7 | | (y^4/5)^2 | | 7900=40x+4000 | | k-4=-7 | | 3(2x-1)=3-2(x-1) | | 4=22x | | -2.2d+16.95=-3.8d-14.41 | | d/-7-8 | | -18+c=-14 | | differentiate:dy/dx=3x^2 | | f(2.3)= | | [(2x-5)/5]-13-x | | Y=9x-2x^2 | | 0.25r+0.75=0.5r | | 2(z+5)-2z=7 |